Intraoperative squash Cytology of diffuse glioma not otherwise specified, of the Cerebellum - Kalogeraki, Alexandra; Tamiolakis, Dimitrios; Zoi, Iris; Segredakis, John; Vakis, Antonios (Acta Biomedica Atenei Parmensis, 2021)
Objective: Diffuse glioma arises anywhere in the CNS, but most frequent in the cerebral hemispheres. The tumor tends to be seen in children and in younger adults aged 20-30. We report one such case in an older female patient presenting the intraoperative cytology of the tumor. Case report: A 48-year-old female was diagnosed by MRI with a tumor of cerebellum. Cytologic material was obtained during the resection of the tumor and diagnosed cytologically as glioma. Conclusion: This case is presented to focus the ability of the intraoperative cytology in diagnosis of the glioma, using immunocytology and confirmed by histo- immunohistology.